Pengembangan Sistem Informasi Monitoring Dan Evaluasi Hasil Kegiatan Pengawas Berbasis Web (Studi Kasus: Dinas Pendidikan Kota Malang) - Aulia Fitri Rahmawati; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The monitoring and evaluation process the results of supervisory activities at Malang City Education Office is done manually. Monitoring process is submitting the results of supervisor activities and supporting data in a document (hardcopy). Evaluating process of supervisor activities result is submitting SKP document that must be transferred to the spreadsheet for the next process. This condition is inefficient and can cause problems like loss of data or files. For this reason, an Information System for Monitoring and Evaluating the Results of Supervisor Activities was developed to help and facilitate the monitoring and evaluation process so the data was organized. The system is built with the waterfall development method and implemented on the website platform. System development has through several stages, they are identifying problems, studying literature, collecting data on system development materials, modeling business processes with BPMN, analyzing requirements, designing with Unified Modeling Language, implementing using the CodeIgniter framework, and system testing with validation testing, compatibility testing, and usability testing. From all of these stages, the results is the system needs 17 features, the result of validation test is â€œvalidâ€ that indicates the system work well like its functionality, the results of compatibility test is â€œcompatibleâ€ for all types of browsers that indicates the system can work on several types of browsers, and the result of usability testing is 80.62 that indicates the information system interface is easy to use and friendly for user.